Studi Fenomenologis Tentang Pemaknaan Religiusitas Pada Mahasiswa Yang Menjalani Hubungan Beda Keyakinan - Fuji Tri Lestari; Juanita Wulan Rohmadhona; Rischo Octavian; Rini Nurahaju (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Religiosity plays a significant role in shaping individuals' perspectives and behavior, particularly when faced with moral dilemmas, such as interfaith romantic relationships. This phenomenon often leads to spiritual and social conflict, where individuals are faced with the choice of maintaining love or obeying their religious teachings. This study aims to understand the meaning of religiosity among college students in interfaith relationships based on the five dimensions of religiosity according to Glock and Stark (1965): ideological, ritualistic, intellectual, experiential, and consequential. This study used a qualitative approach with a phenomenological method. The subjects consisted of three college students in interfaith relationships. Data were collected through semi-structured interviews and analyzed using Interpretative Phenomenological Analysis (IPA). The results show that interfaith relationships generate dynamics including self-growth and reflection, as well as self-conflict related to the conflict between love and religious teachings, the role of the partner and social support, and family pressures that influence individual decisions. Hope for the future of the relationship emerges through perceptions of the partner's flexibility. The implications of this research confirm that the meaning of religiosity is dynamic and influenced by emotional experiences, social support, and family norms. Therefore, support is needed, especially in relationship decision-making.